Cardiovascular autonomic neuropathy in diabetes: Pathophysiology, clinical assessment and implications - Duque, Alice (2021)
Instituto Nacional de Cardiologia. Departamento de Educação e Pesquisa. Rio de Janeiro, RJ, Brasil.